2023
DOI: 10.1093/mnras/stad536
|View full text |Cite
|
Sign up to set email alerts
|

SN 2021zny: an early flux excess combined with late-time oxygen emission suggests a double white dwarf merger event

Abstract: We present a photometric and spectroscopic analysis of the ultra-luminous and slowly evolving 03fg-like Type Ia SN 2021zny. Our observational campaign starts from ∼5.3 hours after explosion (making SN 2021zny one of the earliest observed members of its class), with dense multi-wavelength coverage from a variety of ground- and space-based telescopes, and is concluded with a nebular spectrum ∼10 months after peak brightness. SN 2021zny displayed several characteristics of its class, such as the peak brightness (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 173 publications
2
39
0
Order By: Relevance
“…MUSSES16D4 (Jiang et al 2017) and SN 2018aoz (Ni et al 2022(Ni et al , 2023b, on the other hand, show early red excesses. Normal Type Ia SN 2018oh (Dimitriadis et al 2019a;Li et al 2019;Shappee et al 2019) and overluminous (03fg-like) Type Ia SN 2021zny (Dimitriadis et al 2023) also show early excesses in their high-cadence unfiltered light curves from Kepler 2 and the Transiting Exoplanet Survey Satellite (TESS), respectively, although the color of this excess is not known. An excess can be ruled out in three other SNe Ia with equivalent data from Kepler (Olling et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…MUSSES16D4 (Jiang et al 2017) and SN 2018aoz (Ni et al 2022(Ni et al , 2023b, on the other hand, show early red excesses. Normal Type Ia SN 2018oh (Dimitriadis et al 2019a;Li et al 2019;Shappee et al 2019) and overluminous (03fg-like) Type Ia SN 2021zny (Dimitriadis et al 2023) also show early excesses in their high-cadence unfiltered light curves from Kepler 2 and the Transiting Exoplanet Survey Satellite (TESS), respectively, although the color of this excess is not known. An excess can be ruled out in three other SNe Ia with equivalent data from Kepler (Olling et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent attention has been focused on a handful of SNe Ia that display early excess flux or bumps in their UV/optical light curves relative to a power-law rise. These have been observed in normal SNe Ia (Marion et al 2016;Hosseinzadeh et al 2017;Miller et al 2018;Dimitriadis et al 2019;Wang et al 2023) and a high fraction of peculiar SNe Ia (Cao et al 2015;Jiang et al 2017Jiang et al , 2021De et al 2019;Miller et al 2020;Dimitriadis et al 2023;Srivastav et al 2023). Furthermore, the diversity of early excess flux features in their strength, duration, and color likely suggests that multiple mechanisms can lead to their formation (Jiang et al 2018).…”
Section: Introductionmentioning
confidence: 88%
“…Existing theoretical models have trouble describing all of the characteristic properties of the high-luminosity carbon-rich 03fg-like subclass of SNe Ia. No formal subclassification criteria exist for these events, but these SNe often exhibit broad light curves (Δm 15 (B) < 1.3 mag) and high peak luminosities (M B > −19.5 mag, Howell et al 2006;Yamanaka et al 2009;Scalzo et al 2010), strong carbon absorption and low absorption velocities at early times (Hicken et al 2007;Silverman et al 2011;Chakradhari et al 2014;Parrent et al 2016;Taubenberger et al 2019;Ashall et al 2021), lowionization nebular spectra (Taubenberger et al 2013a;Ashall et al 2021), forbidden calcium emission at late times (Taubenberger et al 2019;Dimitriadis et al 2022Dimitriadis et al , 2023, and early flux excesses (Jiang et al 2017(Jiang et al , 2021Chen et al 2019;Srivastav et al 2023). These SNe also tend to occur in either low-mass host galaxies or remote locations in more massive galaxies, potentially indicating a lower-metallicity progenitor than those of normal SNe Ia (Taubenberger et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest are the origins of excess emission and high-velocity (HV) silicon and calcium lines seen in the early phases, and their relation to the Type Ia SN explosion mechanisms and progenitor systems. Excess emission has been identified within ∼5 days post-explosion in a few normal events (Marion et al 2016;Hosseinzadeh et al 2017;Jiang et al 2018Jiang et al , 2021Dimitriadis et al 2019Dimitriadis et al , 2023Deckers et al 2022;Sai et al 2022), and HV Si II and Ca II features, which are faster than the normal photospheric velocities (PVs) by 7000 km s −1 (Wang et al 2003;Gerardy et al 2004;Quimby et al 2006;Marion et al 2013;Silverman et al 2015), have been observed in a number of normal events before B-band maximum. In the case of the earliest Type Ia SN detected to date, SN 2018aoz, infant-phase excess emission during 1-12 hr since first light showed suppressed B-band flux attributed to line-blanket absorption by surface iron-peak elements (Ni et al 2022(Ni et al , 2023.…”
Section: Introductionmentioning
confidence: 97%